THE IMPLEMENTATION OF FAVORITE PICTURE MEDIA FOR INCREASING SPEAKING SKILL IN DESCRIPTIVE TEXT - Masning Suaidah (Universitas PGRI Madiun, 2019)
The aim of the study is to increase speaking skill in descriptive text by the using of favorite picture media. It is found that there are many students have less interest and activity during English lesson, especially in speaking material. It is because the students get bored during the lesson and the teacher teaches monotonously.. The research design is class action research. Population of this study are 34 students of X MIPA 6 grade SMAN 1 Kawedanan Magetan in first semester, academic year 2017/2018. This research is conducted in two cycles, and each cycle consists of: (1) plan; (2) action implementation; (3) observation; (4) reflection and evaluation. The result of this research shows that in the second cycle, there are 88% or 30 students have good activity during learning process and students’ learning result in average have gained 80 grade, which is maximum passing criteria (KKM) in English lesson is 75. In conclusion, the application of favorite picture media is able to increase speaking skill in the form of descriptive text.